Real-Time Precise Prediction Dispersion Turning Point of Optical Microfiber Coupler Biosensor with Ultra-High Sensitivity and Wide Linear Dynamic Range - Haiyang Yu; Yue Wang; Yang Xu; Wenchao Zhou; Yihui Wu (Biosensors)
Optical microfiber biosensors demonstrate exceptionally ultra-high sensitivity at the dispersion turning point (DTP). However, the DTP is highly susceptible to variations in dimensional and external environmental factors, and the spectral response is mismatched from preparation in air to application in a liquid environment, making the DTP difficult to control effectively. In this work, we propose a method that bridges the relationship between the interference spectra of air and aqueous environments. By counting the interference peaks in air, we can accurately predict the DTP position in liquids. Meanwhile, it provides a new balance between sensitivity and wide linear dynamic range, achieving wide dynamic range detection across various concentrations. The optical microfiber coupler (OMC) is fabricated using the hydrogen–oxygen flame melting tapering method. In addition, the concentration, temperature, and solvent used for the sensor’s biofunctional layer are optimized. Finally, in refractive index sensing, a maximum sensitivity of 1.17 × 105 ± 0.038 × 105 nm/RIU is achieved. For biosensing, a wide dynamic range detection of cardiac troponin I (cTnI) is realized at concentrations of 12–48 ng/mL, 120–480 pg/mL, and 120–480 fg/mL.